2016
DOI: 10.1007/s12528-016-9125-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the self-regulated online learning questionnaire

Abstract: The number of students engaged in Massive Open Online Courses (MOOCs) is increasing rapidly. Due to the autonomy of students in this type of education, students in MOOCs are required to regulate their learning to a greater extent than students in traditional, face-to-face education. However, there is no questionnaire available suited for this online context that measures all aspects of self-regulated learning (SRL). In this study, such a questionnaire is developed based on existing SRL questionnaires. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 38 publications
(56 reference statements)
3
120
0
13
Order By: Relevance
“…And third, regarding construct validity, deeper analysis can be done combining other instruments from the literature, such as those by Barnard et al (2008) or Jansen et al (2016), to gain further insights on learners' motivation and self-regulated learning strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And third, regarding construct validity, deeper analysis can be done combining other instruments from the literature, such as those by Barnard et al (2008) or Jansen et al (2016), to gain further insights on learners' motivation and self-regulated learning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that goal setting and strategic planning are better predictors for attainment of personal course goals. Finally, a recent study by Jansen, Van Leeuwen, Janssen, Kester, and Kalz (2016) proposed another questionnaire for measuring self-regulated learning in MOOCs. In this case, they took as a reference a combination of questionnaires defined in the literature of self-regulated learning and adapted them to the MOOC content.…”
Section: Measuring Motivation and Self-regulated Learning Strategiesmentioning
confidence: 99%
“…Hence, the importance of examining the effect of SRL on improving online learning outcomes cannot be overstated. In this study, we focus on five SRL strategies-metacognitive skills, time management, environmental structuring, persistence, and help-seeking-that have been identified as important skills in online learning (Jansen, van Leeuwen, Janssen, Kester, & Kalz, 2017).…”
Section: Self-regulated Learning Strategies and Online Learningmentioning
confidence: 99%
“…For example, learning dispositions are highly valuable for timely feedback generation (Tempelaar, Rienties, & Giesbers, 2015). In addition, self-regulated learning could be measured to support students' control of their own learning processes in MOOCs (Jansen, van Leeuwen, Janssen, Kester, & Kalz, 2017). Future work should also include these background variables, to obtain a more complete understanding of students' behaviour in the MOOC, which could be used for more personalized improvements and student support.…”
Section: Limitations and Future Workmentioning
confidence: 99%